Mexico - Income Generation and Social Protection for the Poor : Volume 3. An Overview of Social Protection - World Bank (Washington, DC, 2012)
This report provides a strategic overview of Mexico's federal social protection system, comprised of both social insurance and social assistance programs. It assesses its performance to date regarding income risk management for vulnerable groups, and identifies options for stepping up that performance. In doing so it responds to an increasing consensus in Mexico regarding the need for a major social protection policy reform, even if the direction of those reforms is still in flux. The report is designed to provide a first stage diagnostic of major issues facing the social protection system, as an input to ongoing discussion and debate in Mexico, and as a platform for further technical work on the specifics of reform. The report focuses on the role of federal government in the design and implementation of social protection policies, while recognizing that sub-national governments are playing an important role in the provision of these services. In doing so, it draws upon the first phase of the Mexico Programmatic Poverty Work, as well as the urban, rural and vulnerability studies conducted in parallel with this analysis. The report is organized into four chapters. Chapter 1 presents a brief review of social protection concepts, and establishes a framework for determining the optimal role for government in the provision of social protection (risk management) tools, as distinct from market-provided risk management tools, and those undertaken informally by and between households. Chapter 2 discusses the major sources of income vulnerability in Mexico, identifying the major risks that Mexican families faces, and explores the extent to which households have access to private risk management mechanisms for addressing these risks. Chapter 3 provides an overview and assessment of the social protection system in Mexico, and finally Chapter 4 discusses issues and options.